Post-radiation changes of cytoplasmatic calcium concentration in platelets activated by ADP and thrombin - Parkhimovich, Olga G.; Bichan, Olga D.; Bulanova, Klavdiya Ya. (Experimental Biology and Biotechnology, 2023)
In the short term (3rd, 10th and 30th days) after irradiation at a dose of 1 Gy, platelets show an increased basal level of calcium ions in the cytoplasm compared to the control values, both in the presence and in the absence of calcium ions in the external environment. Under the action of ADP (20 µmol/L) and thrombin (0.02 U/mL) under similar conditions, there is an increase in the concentration of calcium ions in the cytoplasm of platelets in the post-radiation period. The most pronounced radiation-induced changes in the content of cytoplasmic calcium in resting and activated platelets are typical for the 3rd day of the post-radiation period. The data obtained indicate that the increased reactivity (resensitisation) of plasma membrane receptors in the short term after irradiation at a dose of 1 Gy creates conditions for the manifestation of hemorrhagic syndrome not only with the development of radiation sickness, but even with low-dose irradiation.